The effect of traditional agricultural practices on the food consumption of households facing extreme weather events in Tanzania - Tim Wegenast; Niklas Hänze; Roos Haer; Marcel Birulés (Agriculture & Food Security)
Abstract Background An estimated 140 million people in Africa face acute malnutrition. By impacting agricultural production, climate change is likely to further decrease food consumption, particularly in sub-Saharan African states. Against this backdrop, various actors have called for more attention to alternative farming and food systems based on traditional agricultural knowledge capable of ensuring access to sufficient, nutritious, and safe food. So far, however, we have limited systematic evidence on which traditional agricultural practices may promote the food resilience of households exposed to extreme climatic conditions. Focusing on the most prevalent traditional diversification practices in Tanzania, this study assesses the extent to which crop diversification, annual crop intercropping, crop-tree intercropping, crop-livestock integration, and the cultivation of traditional crops increase the food availability and dietary diversity of smallholders facing extreme weather events in Tanzania. Methods We combine temperature and rain data with information on farming practices and food consumption information provided by the Living Standards Measurement Study–Integrated Surveys on Agriculture for more than 25,000 Tanzanian households nationwide. We rely on a matched differences-in-differences approach to account for selection bias and allow for causal inference. Results Our matching models consistently show that the planting of traditional crops (in particular sorghum) promotes dietary diversity and reduces the need for food rationing in households experiencing climate shocks. In contrast, households relying on maize cultivation show less dietary diversity and increased food rationing behavior. In addition, we find that—under extreme weather conditions—crop diversification furthers households’ dietary diversity, and crop-livestock integration, as well as crop-tree intercropping, seem to reduce households’ need to ration food. Conclusion and policy recommendation This study has important implications for policymakers. In light of climate change and weather variability, it underscores the need to better integrate indigenous knowledge into farming systems. Our results call for greater dissemination of traditional diversification strategies and more reliance on indigenous, drought-tolerant crops. Traditional farming practices can function as a safety net, protecting smallholders in Tanzania against the detrimental consequences of weather shocks.